2013
DOI: 10.5433/1679-0359.2013v34n2p669
|View full text |Cite
|
Sign up to set email alerts
|

Indirect measurement of photosynthetic pigments in the leaves of Jatropha curcas

Abstract: The aim of this work was to generate mathematical models capable of identifying photosynthetic pigments and soluble proteins from the leaves of Jatropha curcas using the relationship between classical readings performed by spectrophotometry and the chlorophyll meter, ClorofiLOG ® 1030. The work was conducted at Embrapa Cotton, in the city of Campina Grande, state of Paraíba, Brazil. For indirect analysis, portable equipment was used to read leaf discs at different stages of development. The chlorophyll in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…Brito et al (2011) and Rigon et al (2012Rigon et al ( , 2013) also observed a high correlation coefficient among the methods of determination of pigments in cotton, sesame and jatropha, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Brito et al (2011) and Rigon et al (2012Rigon et al ( , 2013) also observed a high correlation coefficient among the methods of determination of pigments in cotton, sesame and jatropha, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Hendry and Price (1993) emphasize that the relationship Determination of photosynthetic pigments in fleabane biotypes ... coffee, with coefficients of determination of 0.92. As for Rigon et al (2013), when using the portable ClorofiLOG determiner for the crop of jatropha, obtained a coefficient of determination of 0.73. A high initial development and the total accumulation of photoassimilates for the resistant biotype may involve high interspecific competitive ability for this species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the SPAD index values, we have calculated the concentrations of chlorophyll a and b and carotenoids, according to Rigon et al (2013) for J. curcas.…”
Section: Chlorophyll Contentmentioning
confidence: 99%
“…Although SPAD-502 measures absorption from leaves at two wavelengths, 660 nm (red) and 940 nm (near-infrared), ClorofiLog measures the absorption at three wavelengths, 635 nm and 660 nm (red) and 880 nm (near infrared - Barbosa et al 2013, Rigoni et al 2013). We expected ClorofiLog, which measures a third wavelength near the second absorption peak of Chl b (642 nm), to provide 832 iForest 9: 829-834 …”
Section: Discussionmentioning
confidence: 99%